Impact of Strontium-Substitution on Oxygen Evolution Reaction of Lanthanum Nickelates in Alkaline Solution - Sankannavar, Ravi; Sandeep, K. C.; Kamath, Sachin; Suresh, Akkihebbal K.; Sarkar, A. (Journal of the Electrochemical Society, 2018)
In the present study, activity for anodic oxygen evolution reaction (OER) has been evaluated by varying the degree of Sr2 + -substitution in La1 − xSrxNiO3 from x = 0.0 to 1.0. EDS was utilized to measure the elemental composition. XRD and Rietveld refinement were employed for the phase and crystal structure analysis. It was observed that the crystal structure of LaNiO3 was distorted after Sr2 + -substitution and formed tetragonal lanthanum-strontium nickelates (LSN) for x ⩽ 0.8, and rhombohedral strontium nickelate for x = 1.0. For all the samples, secondary phases (NiO for 0.2 ⩽ x ⩽ 1.0 and SrCO3 for 0.8 ⩽ x ⩽ 1.0) were also observed. Rietveld analysis suggests that Sr2 + -substitution caused the cell volume to contract. The oxidation state of Ni in the samples were investigated by XPS for the elusive Ni4 + . An increase in the mass specific activity for OER was observed as the degree of Sr2 + -substitution increase until x = 0.6, however, the activity decreased for higher values of x. The LSN samples were significantly more active than that of LaNiO3, and the state-of-the-art electrocatalyst Ba0.5Sr0.5Co0.8Fe0.2O3 − δ.